The effect of incorporating Baccaurea Angulata extract on rheological properties of various gelling polymers - Abdul Qader, Omar Abdul Jabbar; Sukmasari, Susi; Doolaanea, Abd Almonem; Abdul Rahman, Mohammad Nasrin; Ismail, Ahmad Faisal (Association of Indian pharmacist (AIP), 2018)
To Select The Best Gelling Polymer To Be A Vehicle For Baccaurea Angulata Extract (Bae) For Dental Application. This research will open up a new findings and information to the future baccaurea angulata dental gel formulator and developer.Three Different Gelling Polymers; Carbopol, Guar Gum And Konjac Gum, Were Characterized Rheologically With The Incorporation Of 3% W/W Bae. This Includes The Apparent Viscosity At 3 Different Shear Rates (10s-1, 50s-1, And 100s-1), Shear Stress At The Shear Rate Of 100s1 And The Rheological Modelling For Each Of The Gels As Herschel Bulkley Or Ostwald De Waele Model.It Was Found That The Apparent Viscosity Of These Three Gels At Three Different Shear Rate (10s1, 50s-1 , And 100s-1) As Well As Shear Stress (Pas) Needed To Produce Shear Rate Of 100s-1, Decrease In The Gels Incorporated With Bae. Carbopol Incorporated With Bae Had Acceptable Apparent Viscosity, Higher Shear Stress Needed To Produce Shear Rates Of 100s-1, Better Value Of Regression, Yield Stress (Τ0), Consistency Factor (K), And Flow Behavior Index (N) Compared To Guar Gum And Konjac Gum Incorporated With Bae.In Conclusion, Carbopol Could Be The Best Gel Polymer Candidate For Bae Dental Gel Formulation